2016
DOI: 10.1016/j.taap.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Genistein exposure inhibits growth and alters steroidogenesis in adult mouse antral follicles

Abstract: Genistein is a naturally occurring isoflavone phytoestrogen commonly found in plant products such as soybeans, lentils, and chickpeas. Genistein, like other phytoestrogens, has the potential to mimic, enhance, or impair the estradiol biosynthesis pathway, thereby potentially altering ovarian follicle growth. Previous studies have inconsistently indicated that genistein exposure may alter granulosa cell proliferation and hormone production, but no studies have examined the effects of genistein on intact antral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
2
20
2
Order By: Relevance
“…We found that genistein exposure did not affect estradiol and progesterone levels at any time points (Figure 6). Contrary to our results, numerous in vitro studies conducted on adult ovarian cells show that exposure to genistein reduces estradiol biosynthesis and alters progesterone production [19, 27, 28, 38, 39]. One major difference between our study and the previous in vitro studies is the dose selection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that genistein exposure did not affect estradiol and progesterone levels at any time points (Figure 6). Contrary to our results, numerous in vitro studies conducted on adult ovarian cells show that exposure to genistein reduces estradiol biosynthesis and alters progesterone production [19, 27, 28, 38, 39]. One major difference between our study and the previous in vitro studies is the dose selection.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, genistein inhibits steroidogenesis or steroidogenic enzymes in cultured rat pre-antral follicles [22], rat granulosa-luteal cells [23], porcine granulosa, theca, or luteal cells [24–27], and mouse antral follicles [28]. Additionally, studies have shown that genistein exposure alters follicle growth [17], induces follicular atresia [29], inhibits oocyte maturation [30], and inhibits antral follicle growth [28] in rodents. Collectively, these studies show that genistein exposure can affect hormone levels and follicle growth, both of which are necessary for normal female fertility [31].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time, to our knowledge, that the effects of isoliquiritigenin on ovarian sex steroid hormone levels have been investigated. However, our findings are consistent with a few studies examining the effects of other phytoestrogens on the levels of steroid hormones [35, 42–44]. For instance, genistein was found to reduce estradiol and increase progesterone synthesis of cultured mouse antral follicles [35].…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings are consistent with a few studies examining the effects of other phytoestrogens on the levels of steroid hormones [35, 42–44]. For instance, genistein was found to reduce estradiol and increase progesterone synthesis of cultured mouse antral follicles [35]. It was also found to decrease estradiol levels in porcine granulosa cells [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation